Plagiarism Curricula May Reduce Need for Punitive Plagiarism Education - Miller, Robin E. (Evidence Based Library and Information Practice, 2014)
Objective – To describe the development and implementation of two courses designed to help university students avoid plagiarism. Design – Quantitative and qualitative analysis. Setting – A university in the United Kingdom. Subjects – An unknown number of university students who took a Plagiarism Awareness Program (PAP) course between 2008 and 2011, and approximately 3,000 university students enrolled in a Plagiarism Avoidance for New Students (PANS) course delivered via a virtual learning environment (VLE) between October and December 2012. The authors attempted to collect rates of continued plagiarism among students who had taken plagiarism education courses. The authors also surveyed 702 university students about plagiarism in 2011. Methods – Data collected from PAP participants informed revision of the authors’ approach to plagiarism education and led to development of the second course, PANS. At the end of the course, students completed a test of their knowledge about plagiarism. Authors compared scores from students who took a course supervised by a librarian to the scores from students who took the course independently. Main Results – Students reported that many aspects of citation and attribution are challenging (p. 149). The authors discovered that 93% of students who completed the PANS course facilitated by a librarian in-person passed the final exam with a grade of 70% or higher, while 85% of students who took the same course independently, without a librarian instructor, in an online VLE scored 70% or higher (p. 155). The authors report that referrals of students who plagiarized declined significantly (p-value < 0.001) since the implementation of a plagiarism avoidance curriculum. Conclusion – As reported by the authors, first-year university students require more extensive education about plagiarism avoidance. A university plagiarism avoidance program instructed by librarians reduces the total number of students caught plagiarizing and mitigates the need for punitive plagiarism education programs. In discussing the challenges and implementation of plagiarism awareness curricula, the authors contribute to the dialogue about effective approaches to addressing this critical issue in higher education.